The Influence of the Effectiveness of Moral Education and Teacher Exemplary Behavior on the Attitude of Respect (Ta’dzim) among Students at Darussa’adah Al-Islamy Islamic Boarding School, Malang. - Maulana Malik Ibrohim; Munirul Abidin (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
This study aims to analyze the influence of moral learning effectiveness and teacher role modeling on students' attitudes of respect in the face of the challenges of the digital era. The shift in the values of pesantren students' manners, influenced by the global flow of information, is the main problem in this research. In fact, ta'dzim is the essence of the blessing of knowledge, which must be maintained even tho the digital world brings many challenges. The research method used is quantitative with a causal-associative design, where data was collected thru questionnaires distributed to a sample of 227 students using the Stratified Random Sampling technique. To analyze the data, the Multiple Linear Regression technique was used. The research results indicate that the effectiveness of moral education and teacher role modeling have a positive and significant influence on students' attitudes of respect, with a contribution of 55.1% (R2=0.551) based on the F-statistic test (137.268) with a significance value of 0.000. Partially, teacher role modeling (X2) has a more dominant influence (regression coefficient 0.541) compared to the effectiveness of moral learning (X1). The conclusion of this research is that the formation of student character of reverence in pesantren must involve synergy between an effective education system and real-life examples from educators, who can serve as role models in daily life.